Separation of nanocomposites using microfluidic systems adapted with ultrasound (2020)
Nanotechnology has played an essential role in the development of numerous advances we have nowadays. Nanotechnology involves the design of microscopic electronic components, incorporated into the electronic devices used daily in society, and the development of nanocomposites, which have allowed great advances not only on multiple areas of electronics, but also on biotechnology. Nanocomposites are materials designed to incorporate nanoparticles of different physical characteristics into a matrix. They seek to encapsulate different organic materials, within an inorganic matrix, to take advantage of their physical properties in a more efficient way. One of the most recurrent problems that appear while fabricating nanocomposites is the agglomeration of its nanoparticles. This happens because the physical properties that are enhanced within the nanocomposites, makes them stick to each other when they are being synthesized. Because of this, there's not only a reduction on the nanocomposite efficiency, but also it makes it harder to use on nano-metrical...